Long-term Changes in Renal Function, Blood Electrolyte Levels, and Nutritional Indices after Radical Cystectomy and Ileal Conduit in Patients with Bladder Cancer - Miyake, Makito; Owari, Takuya; Tomizawa, Mitsuru; Matsui, Masaru; Nishibayashi, Naoko; Iida, Kota; Onishi, Kenta; Hori, Shunta; Morizawa, Yosuke; Gotoh, Daisuke; et al. (Urology Journal, 2019)
Purpose: To assess the long-term changes in renal function, blood electrolyte levels, and nutritional indices after radical cystectomy and ileal conduit in patients with bladder cancer. Patients and Methods: In 129 patients who underwent radical cystectomy and ileal conduit, we evaluated clinicopathologic features, complications, and the change in the estimated glomerular filtration rate (eGFR) from baseline to 1, 2, 3, 4, 5, and 10 years postoperatively. Two nutritional indices, the geriatric nutritional risk index (GNRI) and prognostic nutrition index (PNI), were calculated with laboratory tests. The Student t-test, Mann-Whitney U test, paired t-test, or Wilcoxon’s signed-rank test was used, as appropriate. Results: In the ileal conduit group, a parastromal hernia was observed in 10% of patients, whereas 13% had an ureteroenteric anastomotic stricture, which was associated with greater decline in the eGFR postoperatively. The first 5 year-decline in the eGFR was 1.74 mL/min/1.73 m2/year. The levels of only potassium showed a significant increase at 1 year postoperatively (mean: 4.34 mEq/L) and remained high compared with the baseline (4.14). Evaluation of the nutritional indices demonstrated that the GNRI, not PNI, showed a significant, transient increase from 1 to 4 years (range: 108?110) postoperatively compared with the baseline (105). Conclusion: The first 5 year-decline was much higher than that among Japanese individuals who participated in an annual health examination program. Further research should be performed to identify an appropriate strategy for selecting the suitable type of urinary diversion and postoperative nutritional interventions to improve the clinical outcome of patients with bladder cancer.